Knowledge worth having in ‘excess’: The value of tacit and firm‐specific human resource slack - Lecuona, Jose R.; Reitzig, Markus (Strategic Management Journal, 2014)
Whether holding resources in excess of what is needed to sustain routine operations (i.e., having slack) increases or decreases firm performance is a question of ongoing interest to management scholars. We contribute to existing theory by arguing that human resource slack generally decreases a firm's performance but that holding excess numbers of employees who possess important tacit knowledge that is specific to firms may benefit the firm. We find that the value of these excess resources increases as firms face competitive pressures and decreases when firms' operational choices facilitate the standardization of workflows. We obtain initial empirical evidence for our predictions by testing them on a novel dataset comprising six years of data for 4,070 manufacturing plants in Mexico . Copyright © 2013 John Wiley & Sons, Ltd.